Concept of place in literary tourism - Nikolić, Jovana (The Business of Tourism, 2022)
The aim of this paper is to depict how the concept of place is presented and interpreted in literatury tourism. Drawing upon the poststructuralist and postmodern theories of culture and tourism the paper will explore the relation between the literary places  and tourists. In other words, the paper examines how the literary places influence visitors’ experiences of certain places and how the visitors assign meanings to the fictional places which exist in the real world and vice-versa (the real places which also exist in the world of fiction). In the context of literary tourism the boundaries between the fictional and non-fictional worlds are inevitably blurred in the tourist’s experience. The tourist becomes the active creator of both, the potential tourist offer and the authentic experience which is personal and subjective. In order to create the appropriate tourist offer to the bibliophiles it is of the utmost importance to understand the way visitors experience such places. In order for the literary place to become popular it is necessary to include several factors including the creative act of the visitor.
Keywords: places; literary tourism; literature; autenticity; experience